Friction between a new low-steel composite material and milled steel for SAFE Dampers. (1st September 2016) - Lee, Chang-Hwan; Ryu, Jaeho; Oh, Jintak; Yoo, Chang-Hee; Ju, Young K.
Highlights: Higher friction coefficient was achieved with a milled steel surface. A new clamping detail incorporating load washers was proposed for better performance. Load washers also functioned to improve real contact conditions of frictional surfaces. The behavior can be confidently predicted by the idealized Coulomb friction model. From NLTHA, the damped system demonstrated effectiveness in reducing structural responses. Abstract: This paper describes the development process of a new low-steel composite friction material and the experiments to investigate its frictional behavior. Automotive braking technology was adapted to derive an optimal friction damper for buildings, and a high friction coefficient and stable behavior were set as the primary targets for performance. To improve performance, clamping details which incorporated load washers were also proposed. In order to evaluate the performance of the friction system, pseudo-dynamic tests were conducted. In the experiments, the proposed friction dampers showed repeatable, predictable, and very stable behavior without significant fading of frictional resistance, even under hundreds of repetitive sliding excursions. The friction load tended to be proportional to the initial clamping force regardless of the real-time clamping force, thus confirming that the behavior of the proposed dampers could be predicted using the idealized Coulomb friction model. It was also verified that frictional performance could be remarkably increased through the use of conical shaped load washers, when applied correctly. Furthermore, nonlinear time history analysis was performed on a five-story example building with and without friction dampers. Based on the results, the friction damped system demonstrated effectiveness in reducing structural responses such as roof displacement, base shear force, and story drift ratio compared to the original undamped frame system.